Multi-layer traffic engineering framework for inter-working multi-hop wireless networks - Salami, Oladayo M (Department of Electrical Engineering, 2014)
The interworking of multi-hop wireless networks can conveniently provide ubiquitous seamless service and continual access for network users. Ubiquity can be achieved through multi-technology mobile terminals (nodes), which enables network users to access any available network. In addition, such nodes extend network coverage by relaying traffic for each other. However, to exploit the benefits of the internetworking, it is desirable to have appropriate traffic engineering (TE) mechanisms. Taking into account the co-existence of different physical and Medium Access Control (MAC) layer standards in the individual networks, the multi-hop communication capability and the impairment-prone wireless medium, TE becomes challenging.